Municipal solid waste generation in mature destinations: An IPAT-type model for Mallorca - Italo Arbulú; Javier Lozano; Javier Rey-Maquieira (Economía Agraria y Recursos Naturales)
Several studies examined the relationship between environmental degradation and population growth. However, most of them don’t take into account the difference between local population and tourist arrivals. This paper contributes to the literature by separating these two groups within the framework of IPAT-based models to measure the impact of tourist arrivals in terms of municipal solid waste generation for Mallorca. The model leads to a stochastic differential equations system, which showed that this mature tourist destinations have higher population elasticity than industrial economies. Moreover, the model allowed us to measure the elasticity of substitution between lower-income and higher-income tourists.